Six ways to get a grip on recruiting “Occasional Faculty Developers” - Hazelton, Lara; Lazor, Jana; Buckley, Heather; Hamilton, Joanne L (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Faculty development involves activities that prepare faculty members to fulfill academic roles as teachers, educators, and leaders. In addition to personnel with specialized expertise in faculty development, most medical schools rely upon the contributions of occasional faculty developers for whom faculty development is not their primary responsibility or area of training. Recruiting occasional faculty developers, many of whom are also clinicians, to support faculty development programming can be challenging. In this article, we provide suggestions for how to successfully recruit and retain occasional faculty developers to provide education to medical faculty on teaching and other academic topics.